Reforming labor markets: Reflections of an economist who (unexpectedly) became the Italian Minister of Labor - Elsa Fornero (IZA Journal of European Labor Studies, 2013)
Technocratic Minister of Labor in an economic emergency, with the assignment to devise two key reforms (pension system and labor market): a unique, though hard experience for an academic, confirming the gap between economic research and real life. This paper gives an account of the Italian labor market reform, an attempt to reconcile economic logic, social expectations, requests from European institutions and financial constraints. This reform survived difficult social dialogue and long Parliamentary debates and had severe communication problems; resulting however in a comprehensive law aiming at inclusion, dynamism and higher productivity and representing a chance of better prospects for the young.
Keywords: J08; 330; Labor reform; Labor law; Italy